2006
DOI: 10.1007/s11064-006-9125-8
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Brain Metabolic Dysfunction as a New Paradigm for Approaching Alzheimer’s Dementia

Abstract: Since its definition Alzheimer's disease has been at the centre of consideration for neurologists, psychiatrists, and pathologists. With John P. Blass it has been disclosed a different approach Alzheimer's disease neurodegeneration understanding not only by the means of neurochemistry but also biochemistry opening new scenarios in the direction of a metabolic system degeneration. Nowadays, the understanding of the role of cholesterol, insulin, and adipokines among the others in Alzheimer's disease etiopathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 171 publications
1
32
0
Order By: Relevance
“…Emerging evidence suggests that APN plays an important role in Alzheimer's disease (AD) [4]. Consistent with this view, we recently showed that APN modulates a metabolic pathway to suppress neurodegeneration in cellular and mouse models of ␣-synucleinopathies, including Parkinson's disease (PD) and dementia with Lewy bodies (DLB) [5].…”
Section: Introductionsupporting
confidence: 57%
“…Emerging evidence suggests that APN plays an important role in Alzheimer's disease (AD) [4]. Consistent with this view, we recently showed that APN modulates a metabolic pathway to suppress neurodegeneration in cellular and mouse models of ␣-synucleinopathies, including Parkinson's disease (PD) and dementia with Lewy bodies (DLB) [5].…”
Section: Introductionsupporting
confidence: 57%
“…NBM has also been reported to participate in memory and sleep/wake regulation [41, 42] and to degenerate in Alzheimer’s disease [6]. Furthermore, clinical and epidemiological studies have proposed a link between obesity/type 2 diabetes and the risk of developing Alzheimer’s disease [8, 43]. The presence of AdipoR1, as was demonstrated in our study, and the previously reported expression of leptin receptors [44] in NBM may suggest possible effects of adipocytokines on cognitive brain functions and a role in the reported obesity-linked risk for dementia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been disclosed a different approach Alzheimer's disease neurodegeneration understanding not only by the means of neurochemistry but also biochemistry opening new scenarios in the direction of a metabolic system degeneration [93]. For example, aconitase and ATP synthase are targets of MDA modification [94]; methylglyoxal is an inhibitor of antioxidant enzymes [95] and it changes structure and function of ceruloplasmin, a serum oxidase carrier of copper ions [96].…”
Section: Discussionmentioning
confidence: 99%